Enhanced pathogenicity by up-regulation of A20 after avian leukemia subgroup a virus infection - Chen, Xueyang; Wang, Xingming; Yang, Yuxin; Fang, Chun; Liu, Jing; Liang, Xiongyan; Yang, Yuying (Frontiers in Veterinary Science, 2022)
Avian leukemia virus subgroup A (ALV-A) infection slows chicken growth, immunosuppression, and tumor occurrence, causing economic losses to the poultry industry. According to previous findings, A20 has a dual role in promoting and inhibiting tumor formation but has rarely been studied in avians. In this study, A20 overexpression and shRNA interference recombinant adenoviruses were constructed and inoculated into chicken embryos, and ALV-A (rHB2015012) was inoculated into one-day-old chicks. The results of an analysis of body weight, organ index, detoxification, antibody production, and organ toxin load revealed that A20 overexpression could enhance the ALV-A pathogenicity. This study lays the foundation for the subsequent exploration of the A20-mediated tumorigenic mechanism of ALV-A.